Cash Waqf Linked Sukuk Alternative Development of Sustainable Islamic Economic Development Sustainable Development Goals (SDG's) - Wina Paul; Rachmad Faudji; Hasan Bisri (International Journal of Nusantara Islam, 2021)
Economic development itself is defined as a continuous process that has the aim of increasing a country's Gross Domestic Product (GDP) and per capita income of a country's population in the long term which has an impact on various aspects, both economic, social, and science and technology. The purpose of economic development in Indonesia is not only to increase per capita income but also to accelerate economic growth. Technological advances as a result of this development will also improve the quality of human resources, improve community welfare, reduce inequality, and reduce unemployment. The government continues to face various forms of economic development problems in Indonesia, including high unemployment, rampant poverty, high population, inflation resulting in low purchasing power, low productivity resulting in low per capita income, and export commodities dominated by the primary sector. Today, the development of Islamic economics, both in academia and practice, is very important to pay attention to. This is also related to how to develop thoughts and applications of the Islamic economic system in Indonesia. Various perspectives in the field of Islamic economics associated with the Sustainable Development Goals (SDGs) themselves were created to answer the demands of world leadership in overcoming poverty, inequality and climate change in the form of real action. Establish a set of targets that can be applied universally and can be measured in balancing the three dimensions of sustainable development such as environmental, social and economic. Islamic economic objectives in several points of view are philosophical goals consisting of Al-Falah (holistic prosperity) and Maqasid al-Shariah and operational objectives consisting of increasing faith, creating maslahah, preventing concentration of wealth, and avoiding dangerous activities and even distribution. On the basis of this Islamic economic objective, the response was the issuance of a Cash Waqf Linked Sukuk as a product of the government through the Ministry of Finance to serve as an alternative to increasing Islamic-based economic development. The method used in this article is descriptive qualitative method with literature review. Through this article, we will try to discuss how this cash waqf linked sukuk can be used as an alternative for sustainable Islamic economic development. Sustainable Development Goals (SDG's).